Abstracts (Edited by Prof. Tahir Mahmood) - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2009)
Corneal biomechanics, thickness and optic disc morphology in children with optic disc tilt Lim L, Gazzard G, Chan Y-H, Fong A, Kotecha A, Sim E-L, Tan D, Tong L, Saw S-M Br J Ophthalmol 2008; 92: 1461-6 Correlation of lens density measured using the Pentacam Scheimpflug system with the Lens Opacities Classification System Ill grading score and visual acuity in age-related nuclear cataract Pei X, Bao Y, Chen Y, Li x Br J Ophthalmol 2008; 92: 1471-5. Second-line therapy with dorzolamide / timolol or latanoprost/timolol fixed combination versus adding dorzolamide/timolol fixed combination to latanoprost monotherapy Konstas AGP, Mikropoulos D, Dimopoulos AT, Moumtzis G, Nelson LA, Stewart WC Br J Ophthalmol 2008; 92: 1498-1502